THE ROLE OF DALIAN NA TOLU CULTURE IN MANDAILING BATAK WEDDING TRADITIONS - Misbahayati Rambe; Muhammad Alfikri (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: This study aims to determine the role of Dalihan Na Tolu culture in Batak Mandailing marriage customs. Descriptive qualitative research was used as the research method. Research data were collected through interviews and literature studies from relevant materials. The data analysis method consists of three stages, namely data reduction, data presentation, and drawing conclusions and verification. The research findings show that Dalihan Na Tolu culture has a strategic role in the Batak Mandailing wedding customs. The Dalihan Na Tolu Institution plays an important role in making decisions. The value system in Dalihan Na Tolu is used as a guide to be used to organize life in carrying out holong (love) between mora, kahanggi and anakboru. Dalihan Na Tolu, is a custom that can penetrate the barriers of religion/belief into a social unit. Dalihan Na Tolu has different positions and functions that can change (dynamically) according to the situation, condition and place. Therefore, the Mandailing people can always adapt if needed. Keywords: Dalihan Na Tolu, Culture, Mandailing Batak